Kajian Pengelolaan Konflik Pemanfaatan Lahan Melalui Mekanisme Ratschap - , MALIK WALADUN SHOLEH RENFAAN; , Ir. Kawik Sugiana, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Ratschap is a traditional custom institution in the South-East Maluku Regency functioned to provide a medium for settling down and resolving various land conflicts. Up to the present time this institution still exist and function well. The research aimed to study the effectiveness of Ratschap in resolving conflicts and to identify the factors affecting it. The research methods used in this research were quantitative and qualitative deductive with a case study approach. The cases are land use conflicts in South- East Maluku whics are Ibra village society against Sathean village society, and the other one of ibra village society against the local government of South-East Maluku This research gethed two kinds of data i.e primary data obtained from some interviews and secondary data obtained from the library references. The research concludes that the effectiveness of conflict resolution is influenced by several factors. Those factors are the little the issue complexity the easier the process of conflict resolving, Internal conflict tends easier to be resolved. But, once both parties are in the different level, it conflict resolution bed not only adat mechanism but the mediation approach as well.